INVESTIGATE THE CRITICAL FACTORS OF SUCCESSFUL GREEN COSMETICS MARKETING - Chan Ting-Yu; Cheng Yu-Jen (PEOPLE: International Journal of Social Sciences, 2025)
Developing effective marketing strategies for successfully green cosmetic marketing is critical for strengthening a company’s competitive advantage and performance. This research adopts the more comprehensive factors and emphasizes the perspectives of senior managers, utilizes the DANP method proposed by Ou Yang et al. (2008) which combines DEMATEL and ANP to examine the major factors of successful green cosmetic marketing. Firstly, the fourteen evaluation criteria are extracted from past literature and are classified into four clusters; then consult with ten scholars/experts; finally, interview with ten senior managers of green cosmetic companies The research results show that the Perceived Value Cluster is the main influence source and The Strategy Diamond Cluster plays as the central role among the four clusters. For green cosmetic companies, the top three priority criteria show that the crucial aspect of business strategy is to identify the means to generate returns by achieving superior quality and a distinctive image across the value chain. To secure a competitive advantage, green cosmetic companies can effectively distinguish themselves from competitors by employing differentiation strategies and prioritizing eco-friendly products to appeal to environmentally conscious customers. Green cosmetic companies focus on product quality, implements differentiation strategies, and prioritizes eco-friendly products. This approach not only meets the rising consumer demand for environmentally conscious products but also enhances the brand’s competitive advantage in the market.